The impact of cultural dimensions on happiness, with special reference to the Member States of the European union. - Juhász, István (Innovation: The European Journal of Social Sciences, 2026)
The research aims to identify a correlation between cultural dimensions and happiness in selected countries and presents a comparative case study based upon Hofstede's and Inglehart-Welzel's Cultural Dimensions. In order to facilitate an understanding of the impact of culture on happiness, the inquiry focused on the Member States of the European Union. Preliminary data analysis revealed a certain extent of correlation between the findings of the Happiness Indexes (World Happiness Report, Eurostat, European Social Survey) and the Hofstede and Inglehart-Welzel models. The analysis suggested that strong positive links can be found in such dimensions as: Survival values and Indulgence. These dimensions have a significant impact on the happiness of the citizens of the respective countries, while the Individualism dimension generates a happiness-enhancing effect as well. A fairly negative link can be established regarding Uncertainty Avoidance and Power Distance. For the other dimensions (Masculinity, Long Term Orientation and Traditional values) the research did not show any significant correlation. The main social implication of this inquiry is that the happier nations in general are more receptive to Survival values and coupled with a more individualistic perspective they are more permissive related to Indulgence.